1984
DOI: 10.1161/01.atv.4.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Intimal injury in vivo activates vascular smooth muscle cell migration and explant outgrowth in vitro.

Abstract: In vivo induced endothelial injury results in an intimal thickening, mainly caused by stimulation of smooth muscle cells (SMC), which migrate into, and proliferate in, the denuded intima. We evaluated the manifestation and persistence of this stimulus in several in vitro explant and growth assays using aortic explants from either balloon catheter-injured rats or from sham-operated controls. SMC outgrowth from control explants started 48 hours after explantation, became half-maximal after 96 hours, with 74% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 23 publications
4
34
1
Order By: Relevance
“…3 Neointimal cells recovered from vascular injury models have been reported as cells that proliferate faster and secrete more extracellular matrix proteins than medial vascular smooth muscle cells, characteristics that persist for many passages in vitro. 45,46 Aneurysmal neointimal cells manifested no significant increase in DNA synthesis or cell proliferation compared with carotid smooth muscle cells and presented decreased basal collagen synthesis in the present study. Reports have suggested that neointimal cells recovered after balloon injury have a blunted response to GFs compared with normal vascular smooth muscle cells.…”
Section: Neointimal Cells and Gfscontrasting
confidence: 62%
“…3 Neointimal cells recovered from vascular injury models have been reported as cells that proliferate faster and secrete more extracellular matrix proteins than medial vascular smooth muscle cells, characteristics that persist for many passages in vitro. 45,46 Aneurysmal neointimal cells manifested no significant increase in DNA synthesis or cell proliferation compared with carotid smooth muscle cells and presented decreased basal collagen synthesis in the present study. Reports have suggested that neointimal cells recovered after balloon injury have a blunted response to GFs compared with normal vascular smooth muscle cells.…”
Section: Neointimal Cells and Gfscontrasting
confidence: 62%
“…27 These results are substantiated by those of other studies that have shown that smooth muscle cells are normally quiescent with respect to proliferation but that deep injuries result in the expression of a phenotype of vascular smooth-muscle cells that exhibits a high proliferative response to other mitogens. 28 Given these results, the aspiration device resulted in a less traumatic acute injury in the vascular wall. However, this study did not analyze the vascular recanalization rate; therefore, deducing that the aspiration device would have better functional results is not appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Smooth muscle cells are dynamic in their organization as illustrated by their infiltration and proliferation in the subendothelium with atherosclerosis, aging, or wall injury. 16 - 17 When grown in culture, smooth muscle cells orient themselves in small colonies or fasciculi of parallel cells, with random overall orientations of these colonies. However, as they proliferate in the subendothelial layer, their orientation is far from random and may be influenced by pulsating circumferential strain, with evidence for this proposal coming from studies of the growth of fibroblasts on cyclically stretched substrates.…”
Section: Discussionmentioning
confidence: 99%